Pengaruh Penambahan Tepung Daun Gamal (Gliricidia Sepium) dalam Wafer Pakan terhadap Kualitas Kimia dan Fisik Sebagai Pakan Ternak Sapi - Bela Vista Rosari Koy; Edelnia Kristina Bere; Muh. Akramullah (Institut Nalanda, 2026)
This study aims to examine the impact of the addition of gamal leaf flour (Gliricidia sepium) in the manufacture of feed wafers on the chemical and physical quality related to cattle feed, as well as determine the most optimal proportion of addition. The research was carried out at the SVD Halikelen Livestock Agriculture Unit, Naekasa Village, West Tasifeto District, Belu Regency for 40 days with four treatments, namely P0 (without gamal flour), P1 (10%), P2 (20%), and P3 (30%). The parameters analyzed included dry ingredients, crude protein, crude fat, crude fiber, as well as physical aspects in the form of color, aroma, and palatability. The results showed that the addition of gamal leaf flour improved the chemical quality of feed wafers, with an increase in dry matter from 72.727% (P0) to 75.344% (P3), crude protein from 12.091% to 15.643%, crude fat from 4.258% to 4.689%, and crude fiber from 8.849% to 10.200%. Physically, the wafer changes color to brownish-green and the distinctive aroma of gamal leaves is getting stronger. Although the P3 treatment showed a longer consumption time, all wafers were still consumed, indicating good palatability. Thus, the P3 treatment with the addition of 30% gamal leaf flour is considered the most effective, because it provides the highest nutritional quality while still being preferred by livestock, so it has the potential to be a strategic local feed ingredient.